Molecular characterisation of Cryptosporidium (Apicomplexa) in children and cattle in Romania - Vieira, Patricia Manuela; Mederle, Narcisa; Lobo, Maria Luisa; Imre, Kalman; Mederle, Ovidiu; Xiao, Lihua; Darabus, Gheorghe; Matos, Olga (Folia parasitologica, 2015)
To investigate the transmission of species of Cryptosporidium Tyzzer, 1907 in Timis County, Romania, 48 isolates of Cryptosporidium coccidia from 11 children, 29 calves and eight pigs were characterised by molecular analysis of two loci (SSU rRNA and 60-kDa glycoprotein gene). Overall, 22 isolates were amplified and sequence analyses revealed that all isolates were Cryptosporidium parvum Tyzzer, 1912. Two subtype families were identified, IIa and IId. Subtype IIdA22G1 (n = 4) was the single C. parvum subtype found in children. Subtypes found in calves included IIdA27G1 (n = 8), a novel subtype, IIdA25G1 (n = 5), IIdA22G1 (n = 2), IIdA21G1a (n = 1), and IIaA16G1R1 (n = 1). Subtype IIdA26G1 was found in a pig. These results were significantly different from previous Romanian reports, as the five subtypes of family IId identified in this study were never identified previously in this country. Thus, cattle may be a source of Cryptosporidium infections for humans and the transmission dynamics of C. parvum in Romania is more complex than previously believed.
Keywords: man; eastern Europe; Cryptosporidium parvum; GP60 variability; calves; molecular epidemiology